Normal Weight pada Lansia: Analisis Body Fat Percentage, Indeks Massa Tubuh, dan Asupan Makronutrien di Panti Bina Lanjut Usia Pos 7 Sentani Kabupaten Jayapura - Elisabet Bre Boli; Dwi Astuti; Oktliana Pasangka; Eldad Onesiforus Sopater Pulo; Hendry Kiswanto Mendrofa (Jurnal Ners, 2026)
This study aimed to analyze the relationship between Body Fat Percentage (BFP) and Body Mass Index (BMI), as well as the influence of energy, carbohydrate, and fat intake on BMI among older adults. A cross-sectional study was conducted involving 35 elderly individuals (7 males, 28 females). BFP was measured using Bioelectrical Impedance Analysis (BIA), macronutrient intake data were obtained through standardized food recall 24-hour and statistical analyses employed Pearson correlation. The mean BMI of subjects was 21.48 ± 3.13 kg/m² (normal range), whereas the mean BFP of 30.48 ± 8.15% approached the obesity threshold. Based on BMI classification, 11.4% of subjects were underweight and 8.6% were overweight. Pearson correlation analysis revealed a statistically significant positive association between BFP and BMI (r = 0.527; p = 0.001) of moderate strength, with BMI accounting for only 27.8% of BFP variance. Multiple linear regression analysis demonstrated that energy intake significantly predicted BMI (p = 0.034), whereas carbohydrate (p = 0.725) and fat intake (p = 0.399) did not exert significant independent effects. The moderate BMI–BFP correlation confirms the limitations of BMI as a sole indicator of body composition in older adults, underscoring the clinical necessity of integrating direct BFP measurement to detect normal weight obesity. Nutritional interventions for the elderly should prioritize achieving adequate total energy intake rather than restricting individual macronutrients